True left-sided gallbladder with variations of bile duct and cholecystic vein - Ishii, Hiromichi (World J Gastroenterol, 2015)
A left-sided gallbladder without a right-sided round ligament, which is called a true left-sided gallbladder, is extremely rare. A 71-year-old woman was referred to our hospital due to a gallbladder polyp. Computed tomography (CT) revealed not only a gallbladder polyp but also the gallbladder located to the left of the round ligament connected to the left umbilical portion. CT portography revealed that the main portal vein diverged into the right posterior portal vein and the common trunk of the left portal vein and right anterior portal vein. CT cholangiography revealed that the infraportal bile duct of segment 2 joined the common bile duct. Laparoscopic cholecystectomy was performed for a gallbladder polyp, and the intraoperative finding showed that the cholecystic veins joined the round ligament. A true left-sided gallbladder is closely associated with several anomalies; therefore, surgeons encountering a true left-sided gallbladder should be aware of the potential for these anomalies.